THE DECLINE AND FALL OF SAGALASSOS. A CERAMIC PERSPECTIVE - Poblome, Jeroen; Bes, Philip; Degryse, Patrick (Rei Cretariae Romanae Fautorum Acta, 2024)
When publishing the first extensive overview of the typology and chronology of Sagalassos Red Slip Ware in 1999, it was concluded that, as far as the end of the local production of tablewares was concerned, this ‘should be situated ... at the end of the sixth or during the first half of the seventh cen- tury AD’. However, ‘a clear chronological yardstick [was] still lacking ... in order to correlate the end of the ceramic production and the abandonment of the site’. Two years later, as reported to the Fautores, ‘the end of the pottery production at Sagalassos became more clear, allowing the definition of a specific ceramic assemblage datable to the second half of the sixth and the first decades of the seventh century AD’. Still, however, ‘more quantified assemblages [were] needed to gauge the importance of imported products and it [was] therefore ... too soon to interpret the wider im- plications for our knowledge of early Byzantine Sagalassos’.